Hydroxyl-rich macromolecules enable the bio-inspired synthesis of single crystal nanocomposites - Yi-Yeoun Kim (Nature Portfolio, 2019)
Calcium carbonate biomineralisation has long been linked to acidic macromolecules. Here, the authors challenge this view and show that a huge number of gold nanoparticles coated with hydroxyl-rich proteins can be incorporated into a calcium carbonate crystal while maintaining single crystal character.